2014
DOI: 10.1007/s13402-014-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction by an analog of curcumin (BDMC-A) in human laryngeal carcinoma cells through intrinsic and extrinsic pathways

Abstract: From our results we conclude that BDMC-A can induce apoptosis in Hep-2 laryngeal carcinoma cells more effectively than curcumin, and that this activity can be attributed to the presence of a hydroxyl group at the ortho position within this compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 51 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…EGFR activates src and the overexpression of src increases the response of EGFRmediated processes. Previously, we showed that BDMC-A was more efficient in binding and inhibiting EGFR signals than curcumin [39]. That finding is consistent with the present finding that BDMC-A treatment reduces expression of src.…”
Section: Discussionsupporting
confidence: 93%
“…EGFR activates src and the overexpression of src increases the response of EGFRmediated processes. Previously, we showed that BDMC-A was more efficient in binding and inhibiting EGFR signals than curcumin [39]. That finding is consistent with the present finding that BDMC-A treatment reduces expression of src.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in caspase-3 enzyme activity serve as important indicators of apoptosis [32]. These changes were examined using a caspase-3 colorimetric assay (BioVision Research Products; San Francisco, CA, USA).…”
Section: Caspase-3 Enzyme Activity Assaymentioning
confidence: 99%
“…During apoptotic cell death, phosphatidylserine (PS), a phospholipid component of the inner-leaflet of cell membranes [32], becomes available at the cell surface. This early marker of apoptotic cell death can be detected by staining with the green fluorescent dye Annexin V-FITC (BD Pharmingen, Germany).…”
Section: Phosphatidylserine Exposure and Cell Permeability Assaymentioning
confidence: 99%
“…Apoptosis is mediated by either an extrinsic pathway, triggered by extracellular stimuli, or by an intrinsic pathway, activated by intracellular modulators [20][21][22][23]. Mitochondria play a critical role in the intrinsic pathway by releasing a series of molecules, including cytochrome c. Within the cytosol, the binding of cytochrome c to adaptor protein Apaf-1 and pro-caspasse-9 molecules leads to the formation of the apoptosome that is responsible for activation of a caspase-dependent apoptotic pathway [24].…”
Section: Introductionmentioning
confidence: 99%